Investigation of Seepage Behavior and Settlement Deformation Mechanisms in Loess Embankment Foundation Systems in Eastern Gansu Province - Wei Wang; Wei Li; Pengxiang Zhang; Lulu Liu (Applied Sciences)
The northwestern region of China is characterized by loess soil and seasonal permafrost. Due to the combined effects of its unique climate and precipitation patterns, local roads frequently suffer from issues such as foundation settlement, erosion, and collapse, which pose significant risks to both road construction and safe operation. This study examines a typical high subgrade in Northwest China, where a scaled laboratory model experiment was conducted. The research investigates the impact of water infiltration at the slope foot, under the dual influences of extreme cold and precipitation, on changes in the internal moisture field and settlement deformation characteristics of both the foundation and subgrade. The results indicate that the variation in moisture content across the section follows an arc-shaped diffusion pattern. Settlement is influenced by both the amount of infiltrated water and cold air, with a noticeable lag effect. A settlement of 0.1 cm is considered the threshold for significant impact, with the minimum observed lag period approaching 4 days. The settlement is concentrated in the slope region, exhibiting a bending failure pattern. Numerical simulations reveal that the cross-sectional settlement distribution forms an inverted “S” shape, and the cumulative moisture content at each monitoring point exhibits a quadratic relationship with the cumulative settlement. The findings of this study provide scientific guidance and technical references for road construction and safe operation in the seasonal permafrost regions of Northwest China.